USING VIDEO BLOGGING IN TEACHING SPEAKING AT THE FIRST GRADE STUDENTS OF SMA-IT AL-FITYAN SCHOOL GOWA - Murnin Ayu Sri Ningsi B.; Ahmad, Djuwairiah; Rauf, Masykur (English Language, Linguistics, and Culture International Journal, 2022)
The purpose of this study was to determine the development of students’ speaking after using the vlogging as medium in learning speaking skills on descriptive text material. This study used a quantitative method with a quasi-experimental group design. The population in this study were students of class X SMA-IT Al-Fityan School Gowa 2021/2022. The total number of students is 60 people. The sample was selected purposively, 15 students from Class XA were selected as the experimental class and 15 students from XB as the control class. The experimental class is taught by Vlogging. Both classes took Pre-Test and post-test. The instrument of collecting data is an oral test that focuses on describing one of the historical place. The results showed that there was a significant difference between the experimental class learning achievements on the post-test. The mean score and standard deviation of the post-test in the experimental class were (M=11.73, SD=1.387). The results of data analysis indicate that the Vlogging technique has a contribution to improve students’ speaking skills in descriptive text material. In implementing vlogging, the researcher found several benefits, the first being that students really enjoyed learning to use vlogging. second, students can used vlogging to demonstrate ideas and give students’ creativity and thirdly in today’s era students easily access the internet and can learn where and whenever they want. Based on the research findings, the researcher concluded that the use of Vlogging as a learning medium was significant to improve students’ speaking skills, especially in descriptive text material.